Evaluation of the Freestyle Optium Neo H point-of-care device for measuring blood glucose concentrations in sick calves - Karapinar, Tolga; Tumer, Kenan Cagri; Buczinski, Sebastien (Wiley, 2020)
Background Data on the performance of a glucometer in calves with different diseases are currently lacking. Objective The primary objective of this study was to evaluate the reliability of a point of care glucometer in calves affected by different diseases relative to a traditional bench-top autoanalyzer. Animals One hundred ninety-six calves with different disorders in a referral hospital. Methods Prospective study. Venous blood samples were used for the determination of glucose concentrations in blood and plasma using the Freestyle Optium Neo H and autoanalyzer, respectively. Data were subjected to Passing-Bablok regression and Bland-Altman plots. The Freestyle Optium Neo H was the test method and the autoanalyzer was the reference method. The diagnostic performance of the glucometer relative to the autoanalyzer was assessed using 3 different plasma glucose concentrations. Results The Passing-Bablok regression for the glucometer against the reference method revealed the presence of both proportional bias (1.12; 95% confidence interval [CI], 1.07-1.18) and constant bias (-11.25; 95% CI, -16.0 to -7.70). The glucometer yielded 92.2%-100% sensitivity and 86.4%-96% specificity for the assessing glucose concentration based on different concentration thresholds. Conclusions and Clinical Importance The Freestyle Optium Neo H showed proportional and constant biases relative to the reference method. The glucometer showed poor performance according to criteria recommended by the International Standards Organization and the American Society for Veterinary Clinical Pathology. However, the glucometer determined hypoglycemia with high sensitivity and specificity therefore it might be used to diagnose hypoglycemia in calves with different diseases until calf-specific POC glucometers are developed.
Keywords: accuracy; bovine; glucometer; precision; sensitivity; specificity